General management - Norrving, Bo (Henry Stewart Talks, 2008)
Organization of stroke care, What is a stroke unit?, Early mobilization, Monitoring of neurological status and vital physiological functions, Blood pressure management, Cardiac care, Oxygen saturation, Blood glucose management, Body temperature, Medical complications, Pain, Swallowing problems, Nutrition, Fall and fractures, Deep venous thrombosis, Urinary tract problems, Seizures
Archived at 2018/12/10